Soluble Urokinase Plasminogen Activator Receptor (suPAR) as a Predictive Biomarker for Renal Failure Stratification and Urinary Tract Infections in Hemodialysis Patients - Ahmed Hasen Kaser Alkarewy; Ali Jalil Ali Alyassery; ahmed.hassen@s.uokerbala.edu.iq (Karbala Journal of Medicine, 2025)
Background: Hemodialysis (HD) is a vital therapeutic intervention for patients with renal failure; however, it is also associated with various health complications, including urinary tract infections (UTIs), which significantly increase the risk of adverse outcomes, This study assessed the role of soluble urokinase plasminogen activator receptor (suPAR) in predicting disease progression, infection severity, and kidney dysfunction in renal failure patients (with/without UTIs) versus controls, determining its potential for early diagnosis and clinical management in hemodialysis populations. Methods: A case-control study was conducted on 90 subjects and compared with 30 healthy controls at Al-Hussein Teaching Medical City Hospital between October 2024 and January 2025. Participants were divided into three groups: Group I included 30 patients with UTI not on hemodialysis; Group II included 30 patients with renal failure and UTI; and Group III included 30 patients with renal failure without UTI. Bacterial pathogens were identified using the VITEK 2 Compact System, and concentrations of suPAR were measured using the sandwich ELISA technique. Results: The prevalence of UTI was significantly higher in females, with E. coli being the most common pathogen. Overall, suPAR levels were markedly elevated in patients with renal failure, both with and without UTI, compared to those in the UTI and control groups. Conclusions: suPAR demonstrated high sensitivity, specificity, and predictive values, suggesting its reliability as a biomarker for early diagnosis and clinical monitoring of renal dysfunction and associated infections. It may serve as a dependable biomarker for renal failure patients and holds promise for diagnostic and prognostic use in clinical settings. Key words: Soluble urokinase plasminogen activator receptor (suPAR), Hemodialysis. Renal failure, UTI